Alterations in cortical and extrastriatal subcortical dopamine function in schizophrenia: systematic review and meta-analysis of imaging studies. (June 2014) - Kambeitz, Joseph; Abi-Dargham, Anissa; Kapur, Shitij; Howes, Oliver D.
Abstract : Background: The hypothesis that cortical dopaminergic alterations underlie aspects of schizophrenia has been highly influential. Aims: To bring together and evaluate the imaging evidence for dopaminergic alterations in cortical and other extrastriatal regions in schizophrenia. Method: Electronic databases were searched for in vivo molecular studies of extrastriatal dopaminergic function in schizophrenia. Twenty-three studies (278 patients and 265 controls) were identified. Clinicodemographic and imaging variables were extracted and effect sizes determined for the dopaminergic measures. There were sufficient data to permit meta-analyses for the temporal cortex, thalamus and substantia nigra but not for other regions. Results: The meta-analysis of dopamine D2 /D3 receptor availability found summary effect sizes of d =–0.32 (95% CI −0.68 to 0.03) for the thalamus, d =–0.23 (95% CI −0.54 to 0.07) for the temporal cortex and d = 0.04 (95% CI −0.92 to 0.99) for the substantia nigra. Confidence intervals were wide and all included no difference between groups. Evidence for other measures/regions is limited because of the small number of studies and in some instances inconsistent findings, although significant differences were reported for D2 /D3 receptors in the cingulate and uncus, for D1 receptors in the prefrontal cortex and for dopamine transporter availability in the thalamus. Conclusions: There is a relative paucity of direct evidence for cortical dopaminergic alterations in schizophrenia, and findings are inconclusive. This is surprising given the wide influence of the hypothesis. Large, well-controlled studies in drug-naive patients are warranted to definitively test this hypothesis.